Data from: Exploring the mechanisms underlying a heterozygosity-fitness correlation for canine size in the Antarctic fur seal Arctocephalus gazella - Hoffman, Joseph I; Forcada, Jaume; Amos, William (Dryad Digital Repository, 2010)
Although heterozygosity-fitness correlations (HFCs) are widely reported in the literature, most studies use too few markers to allow the proximate mechanisms to be convincingly resolved. Two competing hypotheses have been proposed: the general effects hypothesis, in which marker heterozygosity correlates with genome-wide heterozygosity and hence the inbreeding coefficient f, and the local effects hypothesis, in which one or more of the markers by chance exhibit associative overdominance. To explore the relative contributions of general and local effects in a free-ranging marine mammal population, we revisited a strong HFC found using nine microsatellite loci for canine tooth size in 84 male Antarctic fur seals Arctocephalus gazella (Hoffman et al. 2010). Increasing the number of markers to 76, we find that heterozygosity is uncorrelated across markers, indicating that inbred individuals are rare or absent. Similarly, while the HFC based on overall heterozygosity is lost, stochastic simulations indicate that when an HFC is due to inbreeding depression, increasing marker number effectively invariably strengthens the HFC. Together these observations argue strongly that the original HFC was not due to inbreeding depression. In contrast, a subset of markers show individually significant effects, and these are non-randomly distributed across the marker panel, being preferentially associated with markers cloned from other species. Using BLAST searches, we were able to locate 94% of loci to unique locations in the dog genome, but the local genes are functionally diverse, and the majority cannot be linked directly to growth. Our results suggest that inbreeding depression contributes little if at all to the relationship between heterozygosity and tooth size, but that instead the primary mechanism involves associative overdominance. These findings contribute to a growing body of evidence suggesting that general effects are likely to be uncommon in natural populations Fur seal genotypesMultilocus genotypes of 84 dead male ...